Optical coherence tomography: Translation from 3D-printed vascular models of the anterior cerebral circulation to the first human images of implanted surface modified flow diverters. Issue 2 (April 2019) - Martínez-Galdámez, Mario; Escartín, Jorge; Pabón, Boris; Diaz, Carlos; Martín-Reyes, Roberto; Hermosín, Antonio; Crespo, Eduardo; Rodríguez, Claudio; Monedero, Gonzalo; Joshi, Krishna; Lopes, Demetrius K
Background: The new generation of flow diverters includes a surface modification with a synthetic biocompatible polymer, which makes the device more biocompatible and less thrombogenic. Optical coherence tomography (OCT) can be used to visualize perforators, stent wall apposition, and intra-stent thrombus. Unfortunately real world application of this technology has been limited because of the limited navigability of these devices in the intracranial vessels. In this report, we share our experience of using 3D-printed neurovascular anatomy models to simulate and test the navigability of a commercially available OCT system and to show the application of this device in a patient treated with the new generation of surface modified flow diverters. Material and methods: Navigability of OCT catheters was tested in vitro using four different 3D-printed silicone replicas of the intracranial anterior circulation, after the implantation of surface modified devices. Intermediate catheters were used in different tortuous anatomies and positions. After this assessment, we describe the OCT image analysis of a Pipeline Shield for treating an unruptured posterior communicating artery (PCOM) aneurysm. Results: Use of intermediate catheters in the 3D-printed replicas was associated with better navigation of the OCT catheters in favorable anatomies but did not help as much in unfavorable anatomies. OCT image analysis of a PCOM aneurysm treated with Pipeline Embolization Device Shield demonstrated areas of unsatisfactory apposition with no thrombus formation. Conclusions: OCT improves the understanding of the flow diversion technology. The development of less thrombogenic devices, like the Pipeline Flex with Shield Technology, reinforces the need for intraluminal imaging for neurovascular application.